2020
DOI: 10.1007/s00423-020-01948-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute abdomen in patients with SARS-CoV-2 infection or co-infection

Abstract: Purpose Patients with an acute abdomen require emergency surgery. SARS-CoV-2 infection can affect multiple organ systems, including the digestive tract. Little is known about the consequences of COVID-19 infection in emergency surgical patients. Methods Perioperative data for COVID-19 patients undergoing emergency surgery from March 1, 2020, to May 23, 2020 were collected prospectively (NCT04323644). Results During this period, 215 patients u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 18 publications
1
26
0
2
Order By: Relevance
“…of acute abdominal pain. The possibility of digestive manifestations in approximately 10% of cases, due to the binding of SARS-Cov-2 at the level of ACE receptors in the intestinal tract, with fever, abdominal pain, nausea, vomiting, transit disorders, presents with a new element of differential diagnosis on which the on-call surgical team must investigate and exclude (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Moreover, laboratory tests may show an increase in transaminases and amylases in these patients, suggesting hepatic or hepatopancreatic involvement (26)(27)(28)(29).…”
Section: Sars-cov 2 Infection-a Novel Cause Of Differential Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…of acute abdominal pain. The possibility of digestive manifestations in approximately 10% of cases, due to the binding of SARS-Cov-2 at the level of ACE receptors in the intestinal tract, with fever, abdominal pain, nausea, vomiting, transit disorders, presents with a new element of differential diagnosis on which the on-call surgical team must investigate and exclude (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Moreover, laboratory tests may show an increase in transaminases and amylases in these patients, suggesting hepatic or hepatopancreatic involvement (26)(27)(28)(29).…”
Section: Sars-cov 2 Infection-a Novel Cause Of Differential Diagnosismentioning
confidence: 99%
“…The thrombotic causes can be related to the direct invasion of ACE receptors in vascular endothelium, direct viral invasion of the blood vessels, or occlusion resulting from microthrombi formation and include mesenteric vessel ischemia (occlusive or non-occlusive), renal vessel infarcts, and omental infarcts (32). Non-thrombotic causes reported in the literature include pancreatitis, peritonitis, colonic distension, and colitis, and are related to the tropism of the virus to the ACE receptors along the digestive tract (34)(35)(36)(37)(38).…”
Section: Sars-cov 2 Infection-a Novel Cause Of Differential Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few reports have specifically evaluated emergency abdominal surgery outcomes in hospitalized patients already under treatment for COVID-19 respiratory failure. Seeliger et al described six patients, 50% of which developed acute respiratory distress syndrome (ARDS), and 33% died [ 19 ]. The same study also showed that, in seven patients with acute abdomen and SARS-CoV-2 coinfection with mild or no respiratory compromise, mortality was 14.3%, while 28.5% developed postoperative pulmonary complications.…”
Section: Discussionmentioning
confidence: 99%
“…In order to ensure timely publication of our article “Acute abdomen in patients with SARS-CoV-2 infection or co-infection” [ 1 ], the reported follow-up was a minimum of 4 weeks for all patients who underwent emergency abdominal surgery during their COVID-19 disease. It is of importance to address the long-term outcome of surgical procedures, and particularly to determine if patients with an acute abdomen have an increased mortality risk due to a SARS-CoV-2 infection.…”
mentioning
confidence: 99%